On the nature of active sites for formic acid decomposition on gold catalysts. Issue 11 (8th May 2019) - Li, Sha; Singh, Suyash; Dumesic, James A.; Mavrikakis, Manos
Abstract : Atomic scale size-sensitivity of the catalytic properties of sub-nanometer gold clusters for HCOOH decomposition. Abstract : Formic acid decomposition has been studied experimentally on supported gold nanoparticles with strong evidence showing the critical role of gold clusters in the subnanometer range in catalyzing the reaction. However, there is a lack of theoretical studies capable of explaining these experimental observations. In this work, without accounting for support effects, vapor phase formic acid decomposition was studied systematically on sub-nanometric gold clusters from Au4 to Au25, among which several candidate Au clusters were identified as promising active site models for Au/SiC catalysts. Combining theoretical and experimental results suggested that the active site on Au/SiC catalysts could be represented by an Au18 cluster, on which the reaction rates calculated from the microkinetic model closely match the experimentally measured rates. On Au18, formic acid decomposition proceeds through the same formate mediated pathway as that on extended Au surfaces (HCOOH → HCOO + H → CO2 + 2H → CO2 + H2 ), with the reaction taking place on a triangular Au3 site where the reactive Au atoms have a coordination number of 5. Despite the fact that other Au clusters among those studied, including Au17 and Au19, also expose the same triangular Au3 site, they were not found to be an accurate representation of the active sites, suggesting an atom-specific activity of gold clusters for formic acid decomposition.